Effects of balance taping using kinesiology tape in a patient with moderate hallux valgus: A case report. Issue 46 (November 2016) - Lee, Sun-Min; Lee, Jung-Hoon
Abstract: Background: Hallux valgus, an increased angle of lateral deviation in the big toe, can cause pain and difficulties in balancing and walking. This study aimed to investigate the effects of balance taping using elastic therapeutic tape on moderate hallux valgus. Methods: When she walked with shoes, she complained of pain over the medial eminence of the hallux metatarsophalangeal (MTP) joint. Balance taping using kinesiology tape was applied for 3 months (average, 16hours/d) to both big toes of a 26-year-old woman with moderate hallux valgus. Results: On the right side, the hallux valgus angle (HVA) decreased from 21° to 14° and the intermetatarsal angle (IMA) decreased from 15° to 14.5°. On the left side, the HVA decreased from 22° to 11° and the IMA decreased from 15° to 12°. Furthermore, the patient was able to walk long distances in shoes without pain in the medial eminence of the hallux metatarsophalangeal joint. Conclusion: This study suggested that repeated balance taping with kinesiology tape could be used as a complementary treatment method for moderate hallux valgus.